Harnessing the mTOR Pathway for Tuberculosis Treatment - Singh, Pooja; Subbian, Selvakumar (Frontiers in Microbiology, 2018)
Tuberculosis (TB) remains as one of the leading killer infectious diseases of humans. At present, the standard therapeutic regimen to treat TB comprised of multiple antibiotics administered for a minimum of six months. Although these drugs are useful in controlling TB burden globally, they have not eliminated the disease. In addition, the lengthy duration of treatment with multiple drugs contributes to patient non-compliance that can result in the development of drug resistant strains (MDR and XDR) of Mycobacterium tuberculosis (Mtb), the causative agent of TB. Therefore, new and improved therapeutic strategies are urgently needed for effective control of TB worldwide. The intracellular survival of Mtb is regarded as a cumulative effect of the host immune response and the bacterial ability to resist or subvert this response. When the host innate defensive system is manipulated by Mtb for its survival and dissemination, the host develops disease conditions that are hard to overcome. The host intrinsic factors also contributes to the poor efficacy of anti-mycobacterial drugs and to the emergence of drug resistance. Hence, strengthening the immune repertoire involved in combating Mtb through host-directed therapeutics (HDT) can be one of the approaches for effective bacterial killing and clearance of infection/disease. Recently, more scientific research has been focused towards HDT strategies that empowers host cells for effective killing of Mtb, reduce the duration of treatment and/or alleviates the development of MDR/XDR, since Mtb cannot develop resistance against a drug that targets the host cell function. Autophagy is a conserved cellular process critical for maintaining cellular integrity and function. Autophagy is regulated by multiple pathways that are either dependent or independent of mTOR (mechanistic target of rapamycin; a.k.a. mammalian target of rapamycin), a master regulatory molecules that impacts several cellular functions. In this review, we summarize the role of autophagy in Mtb pathogenesis, the mTOR pathway and, modulating the mTOR pathway with inhibitors as potential adjunctive HDT, in combination with standard anti-TB antibiotics, to improve the outcome of current TB treatment.